PELATIHAN PERENCANAAN BERBASIS DATA PADA PENGAWAS SEKOLAH, KEPALA SEKOLAH DAN GURU MENGGUNAKAN METODE INDENTIFIKASI, REFLEKSI DAN BENAHI (IRB) SECARA DARING - Fauzi, Achmad; Rahayu, Rizka Putri; Khair, Husnul; Maulita, Yani (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Data-based planning training is carried out online based on various sources which can be used to carry out or prepare an agenda for future activities and budgets. The data-based planning training activity was carried out online for two days. This implementation started with the experience of the school principal sharing his experience with the education unit in planning and compiling activities and making budgets at the school, then the facilitator provided reinforcement for data mining from the independent teaching platform (PMM ), Education Report Card Platform as well as through data sourced from the North Sumatra Education Quality Assurance Center (LPMP). Then the facilitator reflects on the training on the material that has been explained. On the second day of implementation, each educational unit grouped to discuss and fill in the evaluation sheet, then carried out identification, reflection and improvement in planning activity plans and preparing budgets for the unit, then apart from that, the educational units held discussions to make follow-up plans starting from the date, unit involved and the media used. Next, reflect on your experience at school, then work on an evaluation worksheet that is synchronized with the Identification worksheet, then a reflection worksheet and a fix worksheet, then the education unit finishes working on an activity plan that comes from several data and can prepare a budget that is planned for the long term.